2020
DOI: 10.1002/fld.4832
|View full text |Cite
|
Sign up to set email alerts
|

Spring‐network model of red blood cell: From membrane mechanics to validation

Abstract: Summary Red blood cell membrane is highly elastic and proper modeling of this elasticity is essential for biomedical applications that involve computational experiments with blood flow. Inseparable and often some of the most difficult parts of modeling process are verification and validation. In this work, we present a revised model, which uses a spring network to represent the cell membrane immersed in a fluid and has been successfully used in blood flow simulations. We demonstrate the validation steps by fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
(104 reference statements)
1
10
0
Order By: Relevance
“…We have investigated the inclination angle in [ 39 ] and confirmed that our model corresponds to the experimental measurements of the inclination angle reported in [ 40 ]. Further, in [ 34 ] we performed computational experiments of tank-treading frequency also reproducing the experimental results and thus validating the model.…”
Section: Design and Implementationsupporting
confidence: 55%
See 2 more Smart Citations
“…We have investigated the inclination angle in [ 39 ] and confirmed that our model corresponds to the experimental measurements of the inclination angle reported in [ 40 ]. Further, in [ 34 ] we performed computational experiments of tank-treading frequency also reproducing the experimental results and thus validating the model.…”
Section: Design and Implementationsupporting
confidence: 55%
“…The correspondence is however not direct. The linking of PyOIF elastic parameters to the mechanical properties of cell membrane is described in detail in [ 34 ]. We use values (in lattice units) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We work with an RBC model that we previously developed and introduced in [ 17 , 18 ]. The model consists of two principal components: the fluid and elastic objects immersed in it.…”
Section: Rbc Model and The Concept Of Dissipative Particlesmentioning
confidence: 99%
“…In this work, we employ a novel approach to taking the viscosity contrast into account. We extend the existing red blood cell model based on lattice-Botzmann method (LBM) for governing the fluid and spring network for governing the elasticity of cell membrane [ 17 , 18 ]. We include dissipative particles (DPs) inside the cell as a coarse-grained hemoglobin model to increase the viscosity of the resulting suspension inside the cell.…”
Section: Introductionmentioning
confidence: 99%